Study on the microstructures and tensile creep behaviors of extruded dilute Mg–Mn–Zn alloys - Jianhua Chen; Weiying Huang; Bing Liu; Hiromi Nagaumi; Xuyue Yang (Journal of Materials Research and Technology, 2023)
In this work, creep behaviors of dilute Mg–Mn–Zn alloys were investigated in extruded rods (ER) with bimodal grain microstructures and extruded sheets (ES) with homogeneous microstructures. Tensile creep tests were carried out at 423 K along the extrusion direction (ED) and transverse direction (TD). For brevity, the samples were named as ER-ED, ER-TD, ES-ED and ES-TD, respectively. All samples' creep is dominated by dislocation movement, and different types of dislocation slip are seen in the different samples under loading along each direction. For the ER sample, the creep mechanisms of the ER-ED sample were determined to be cross-slip accompanied by pyramidal <c+a> slip. Differently, the creep of the ER-TD sample was dominated by basal slip and accompanied by grain boundary bulging, which induced the worst creep resistance. For the ES alloy, the creep mechanisms were pyramidal <c+a> and cross-slip, but the cross-slip density of the ES-ED sample was higher. Accordingly, the creep test results indicated that the creep resistance was ranked in an order of ES-TD/ED > ER-ED » ER-TD. Furthermore, bimodal grain microstructure accelerates creep at a similar texture effect level, where grain boundary bulging was clearly observed, as well as the decreased KAM and increased fraction of M/HABs (middle-to-high angle boundaries). These typical softening characteristics might be responsible for weakening the ER-ED sample from the highest room-temperature yield strength to the inferior creep resistance to ES-TD/ED samples, meaning the thermal instability of this strong heterogeneous microstructure.